Effect of Prone Position on Oxygenation in Patients Undergoing Mechanical Ventilation - Sh.S Bassampour; M Aliasgharpoor; A Mehran; A Prizad (Tehran University of Medical Sciences, 2009)
Background & Aim: One of the nurses' roles in patient care is frequent position change in patients undergoing mechanical ventilation. Because of attaching many lines and tubes to these patients, they are in supine or lateral positions most of the time. Nurses prefer these positions due to making care simple. Many studies have shown that prone position has positive effects on oxygenation and ventilation. However, other studies have shown some negative effects. The aim of this study was to determine the effect of prone position on oxygenation in patients undergoing mechanical ventilation. Methods & Materials: In this quasi-experimental study, 36 patients were selected using simple sampling method. Data were collected using a questionnaire and oxygenation data sheet. First, patients were put in supine position. After 30 and 120 minutes, oxygenation was assessed. Then they were changed to prone position and after 30 and 120 minutes oxygenation was reassessed. Data were analyzed using paired t test, spearman, and fisher exact tests in SPSS. Results: The results indicated that there was significant differences between prone position and the amount of spo2 and sao2 oxygenation after 30 and 120 minutes (P<0.001). Conclusion: Prone positioning was effective on oxygenation after 30 and 120 minutes so nurse should use this position in their care.